The Living Theatre’s Antigone in San Sebastian The show that awakened the Avant-garde Basque Art and Theatre Idoia GEREÑU: Teatroa eta euskal arte abangoardista esnarazi zuen ikuskizuna - Gereñu Odriozola, Idoia (EGAN, 2023)
1967. Donostia. The Living Theatre of the United States was invited by the Jarrai theatre group to the Victoria Eugenia, and left a great mark on theatre and Basque art, in general. The participants of Living Theatre interpreted only once their own Antigone, the almost three-hour show, based on the text of Brecth. The new generation of Basque artists who had already taken the lead previously to the avant-garde trend, the ones who supported the new theatre, had irrefutable memories of that day, of that experience. All systematic schemes were broken by the antiquities of experimental theatre, both in terms of performance and in terms of normative human behaviour; and the spectacle left no one indifferent. Under Francos censorship some basques had been seduced by the company; others had been displeased. Over the years, the impact of this performance has left a legacy in Basque theatre and the arts.